Additive effects of steam addition and HBr doping for CaO-based sorbents for CO2 capture - Gonzalez,B; Blamey,J; Al-Jeboori,MJ; Florin,NH; Clough,PT; Fennell,PS (Chemical Engineering and Processing: Process Intensification, 2015)
Calcium looping is a developing CO2 capture and storage technology that employs the reversible carbonation of CaO (potentially derived from natural limestone). The CO2 uptake potential of CaO particles reduces upon repeated reaction, largely through loss of reactive surface area and densification of particles. Doping of particles has previously been found to reduce the rate of decay of CO2 uptake, as has the introduction of steam into calcination and carbonation stages of the reaction. Here, the synergistic effects of steam and doping, using an HBr solution, of 5 natural limestones have been investigated. The enhancement to the CO2 uptake was found to be additive, with CO2 uptake after 13 cycles found to be up to 3 times higher for HBr-doped limestones subjected to cycles of carbonation and calcination in the presence of 10% steam, in comparison to natural limestone cycled in the absence of steam. A qualitative discussion of kinetic data is also presented.